2019
DOI: 10.14309/ajg.0000000000000413
|View full text |Cite
|
Sign up to set email alerts
|

Is Dyssynergic Defecation an Unrecognized Cause of Chronic Constipation in Patients Using Opioids?

Abstract: OBJECTIVES: The impact of opioids on anorectal function is poorly understood but potentially relevant to the pathogenesis of opioid-induced constipation (OIC). To evaluate anorectal function testing (AFT) characteristics, symptom burden, and quality of life in chronically constipated patients prescribed an opioid (OIC) in comparison with constipated patients who are not on an opioid (NOIC). METHODS: Retrospective analysis of prospectively collected data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The Rome IV criteria define OIC as a change in bowel habit or defecatory patterns, in comparison with normal following initiation, alteration, or an escalation in opioid therapy, see Table 1 20 . Two recent cross‐sectional studies comparing symptoms and results of diagnostic testing in constipated patients either currently taking or not taking opioids have shown that opioid use is associated with increased symptom severity, diminution in quality of life, and a greater incidence of rectal hyposensitivity, functional EDs/dyssynergic defecation, and delayed whole‐gut transit 112,113 …”
Section: Clinical Associationsmentioning
confidence: 99%
“…The Rome IV criteria define OIC as a change in bowel habit or defecatory patterns, in comparison with normal following initiation, alteration, or an escalation in opioid therapy, see Table 1 20 . Two recent cross‐sectional studies comparing symptoms and results of diagnostic testing in constipated patients either currently taking or not taking opioids have shown that opioid use is associated with increased symptom severity, diminution in quality of life, and a greater incidence of rectal hyposensitivity, functional EDs/dyssynergic defecation, and delayed whole‐gut transit 112,113 …”
Section: Clinical Associationsmentioning
confidence: 99%
“…In 3,452 patients with chronic constipation, Nojkov et al showed that opioid users (n = 588) had a significantly higher mean defaecatory desire volume (DDV) than non-users. 4 In another study of 424 patients, recent opioid use (but not distant use) was independently associated with higher thresholds of first constant sensation volume, DDV and maximum tolerable volume in a multivariable regression analysis. 5 We also demonstrated, in 2,754 patients referred for specialist investigation for chronic constipation, that opioid use for moderate-to-severe pain (n = 238 patients) was associated with rectal hyposensitivity (defined as ≥2 out of 3 rectal sensory thresholds above normal limits).…”
mentioning
confidence: 95%
“…[7][8][9] OIC results from the binding of opioids to μ-opioid receptors located in the enteric nervous system leading to decreased gastrointestinal motility, reduced intestinal fluid and electrolyte secretion and increased reabsorption, and sphincter dysfunction. [10][11][12] OIC commonly persists with chronic opioid use, whereas other adverse effects such as nausea and vomiting lessen over time. [13][14][15] Gastrointestinal symptoms associated with OIC include decreased stool frequency, straining, hard stools, and a sense of incomplete evacuation.…”
Section: Introductionmentioning
confidence: 99%